Attitudes towards Importance of Foreign Language of Senior High School Students in Fourteen Southern Provinces - Purinthrapibal, Sirima; Castillo, Audrey (Journal of International Studies, Prince of Songkla University, 2017)
This research article aimed to study the attitudes towards importance of foreign language of senior high school students from the fourteen southern provinces of Thailand. The samples were 549 senior high school students learning French in the second semester of 2010 academic year from 32 secondary schools in the fourteen southern provinces. Multistage sampling including purposive sampling and random sampling was employed in the first and second stages respectively. A questionnaire was used as a research instrument. The research findings showed that all of the senior high school students studying French in the fourteen southern provinces thought that English and Chinese were the most important foreign languages in Thailand ( = 4.90 and 4.40), while French and Japanese languages were very important ( = 3.74 and 3.63). For other foreign languages, these students thought that they were moderately important: German ( = 3.08), Korean ( = 3.40), Spanish ( = 2.84), Italian ( = 2.82), Russian ( = 2.77), Malay ( = 2.61), Portuguese ( = 2.60) and Arabic ( = 2.59)